Associations between nutrition knowledge, protein-energy intake and nutritional status of adolescents - Antika Prycilla Veronika; Theresia Puspitawati; Ayu Fitriani (Journal of Public Health Research, 2021)
Background: Adolescence is a period of life with specific health and developmental needs. Nutrition in adolescents is necessary to be considered because it has to be in a  balanced form. The data of Sleman District Health Office 2016 showed that 114 adolescents in Public Health Center of Mlati 1 had undernutrition. Also, it showed that the highest prevalence was at Vocational High School of Muhammadiyah Mlati, which was 42% male and 31% female students. This study aims to know the association of nutrition knowledge, protein-energy intake and adolescents’ nutritional status at Vocational High School of Muhammadiyah Mlati, Sleman Yogyakarta. Design and Methods: This was an observational analytical study with a cross-sectional design. The subjects were adolescents aged 15-18 years, selected using stratified random sampling with a total of 58 persons. Data collected were analyzed using the Spearman Rank Correlation for bivariate technique (where α = 0.05). Results: It was shown that 81.0%  had a good nutrition knowledge, 91.4% had deficit energy intake, 82.8 %  had deficit protein intake, and 58.6% had severe nutritional status. Bivariate analysis showed that there was no significant relationship between nutrition knowledge and nutritional status (p=0.394), but energy intake and nutritional status were related (p=0.010 <α = 0.05). Furthermore, protein intake and nutritional status had a significant relationship (p=0.039 <α = 0.05). Conclusions: To be concluded,  there was a correlation between the protein and energy intake and nutritional status of adolescents.